Devastating Outcomes of Traditional Enemas: Unusual Indications for Well-Known Operations - Cleopatra Mshumpela; Giulia Brisighelli; Chris Westgarth-Taylor (Georg Thieme Verlag KG, 2020)
Background Despite serious health risks having been described, traditional enemas are still often used in African traditional medicine. We aim to report two cases of complications secondary to traditional enemas, to illustrate how severe the injuries can be, and to describe the use of a Swenson type endoanal pull-through and a posterior sagittal anorectoplasty (PSARP) as surgical options. Case Description A 2-year-old girl presented with a necrotic rectum after a traditional enema administration. At admission, she required a laparotomy, colostomy fashioning, and extensive debridement of her rectum and perineum. She subsequently had a pull-through of the descending colon using a PSARP approach, a covering loop ileostomy, and a Malone Antegrade Continence Enema. The ileostomy was reversed at the age of 3 years of age and she is now clean with rectal washouts. The second case was a one- and a half-year-old boy with full-thickness burns to the perineum and rectum secondary to a hot-water enema. A colostomy was initially brought out and pulled through 7 months post the initial surgery. He is now growing well and is fully continent to stools. Conclusions The potential complications associated with the practice of administering at-home enemas can be quite devastating. A transanal pull-through and a PSARP have been proven to be successful techniques in patients who have suffered rectal burns due to traditional enemas.